Preparation method of hafnium carbonitride material, thermal spraying powder and application of thermal spraying powder
By preparing hafnium carbonitride coating on the surface of refractory metals, the problem of reduced mechanical properties of refractory metals in high temperature environments is solved, and the thermal protection capability of high temperatures is significantly improved.
Patent Information
- Application Number
- CN202411770991.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
When used in high-melting point refractory metal materials in high-temperature environments, their high-temperature resistance performance is poor and their mechanical properties are rapidly reduced.
Using the preparation method of hafnium carbonitride material, a high-performance hafnium carbonitride material is prepared by mechanically mixing hafnium carbonitride powder and hafnium nitride powder, vacuum hot press sintering, and atomic-grade solid-solution hafnium nitride coating is prepared by supersonic plasma spraying technology.
The hardness and elastic modulus of the hafnium carbonitride coating are improved, and the thermal protection capability at a high temperature is enhanced. It can last for 80 seconds in a plasma ablation environment of 2600°C, effectively protecting the refractory metal matrix from oxidative ablation damage.
Smart Images

Figure CN119569113A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating materials, and in particular to a preparation method of a hafnium carbonitride material, a thermal spray powder and uses thereof, and in particular to a preparation method of a hafnium carbonitride material, a thermal spray powder of a hafnium carbonitride material and a preparation method of an atomic-level solid solution hafnium carbonitride coating. Background Art
[0002] At present, the development of high-speed flight technology has put forward an urgent demand for high-performance thermal structural materials. Advanced spacecraft need to fly in harsh environments such as high-intensity airflow and high-temperature environments (above 2000°C). Therefore, the preparation of high-temperature resistant and ablation-resistant materials is of particular importance for providing effective thermal protection for hot end components in aircraft systems. Carbides and nitrides of transition metals (IVB and VB groups) have attracted much attention due to their unique combination of physical and chemical properties, such as high melting point, high hardness, and high thermal conductivity. Transition metals can also form complex ternary compounds, which in most cases have better mechanical and chemical properties than binary compounds, due to the hybridization of electron orbitals when replacing atoms in metal and non-metal sublattices.
[0003] CN104557043A discloses a method for preparing a zirconium carbide-silicon carbide-silicon nitride ultra-high temperature ceramic composite material, which belongs to the field of ceramic-based composite materials and solves the problems of difficult sintering and low fracture toughness of existing ZrC-based ultra-high temperature ceramics. The zirconium carbide-silicon carbide-silicon nitride ultra-high temperature ceramic composite material of the present invention is made of zirconium carbide powder, silicon carbide powder and silicon nitride powder. The preparation method is as follows: 1. Weigh the raw material powder according to volume percentage, and obtain slurry after ball milling wet mixing; 2. Evaporate and dry the slurry, and obtain a mixed powder after grinding; 3. The mixed powder is hot-pressed and sintered, and taken out after cooling with the furnace to obtain a zirconium carbide-silicon carbide-silicon nitride ultra-high temperature ceramic composite material.
[0004] At the same time, as the flight speed of aircraft continues to increase, more stringent requirements are placed on the thermal protection system; the key high-temperature structural materials of aircraft are mainly refractory metals and their alloys. Refractory metals (mainly including VB-VIIB group metals tantalum, niobium, tungsten, molybdenum, and rhenium) and their alloys have excellent high-temperature mechanical properties and good room-temperature processing performance.
[0005] However, refractory metals and their alloys have high oxygen affinity and large oxygen solubility, and begin to suffer serious component loss at temperatures far below the extremely high temperatures encountered during high-speed flight. For example, tantalum and niobium will experience "pesting" oxidation at around 600°C, quickly causing catastrophic damage to the material; and tungsten and molybdenum will begin to form volatile oxides at temperatures above 750°C in the air, causing the material's mechanical properties to drop sharply. The failure of refractory metals in high-temperature oxygen-containing environments has seriously restricted their application and development as high-temperature structural components.
[0006] In summary, existing high-melting-point refractory metal materials still have poor high-temperature resistance, and their mechanical properties will rapidly decrease when used in high-temperature environments. In order to solve this problem, by preparing a thermal protective coating on the surface of refractory metals, both the high-temperature mechanical properties and the antioxidant properties of the base material can be taken into account, which is considered to be an effective method to improve the high-temperature antioxidant ablation properties of refractory metals. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a preparation method of hafnium carbonitride material, thermal spray powder and its use, so as to solve the problem that the existing high-melting point refractory metals still have poor high temperature resistance and their mechanical properties decrease rapidly when used in high temperature environment.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a hafnium carbonitride material, the preparation method comprising:
[0010] Mechanically mixing hafnium carbide powder and hafnium nitride powder to obtain mixed powder;
[0011] The obtained mixed powder is subjected to vacuum hot pressing and sintering to obtain a hafnium carbonitride material;
[0012] The absolute vacuum degree of the vacuum hot pressing sintering is ≤0.1 mbar; the insulation temperature of the vacuum hot pressing sintering is 2000-2200° C.; and the pressure applied by the vacuum hot pressing sintering is 35-45 MPa.
[0013] The preparation method provided by the present invention realizes the preparation of high-performance hafnium carbonitride material with good mechanical properties by adopting a specific preparation process; compared with the hafnium carbide coating material, the hardness and elastic modulus of the hafnium carbonitride coating are respectively improved by more than 28.8% and more than 25.3%, which are 16.92±0.52GPa and 159.45±7.32GPa respectively; the coating obtained by further thermal spraying can withstand 80s in the ablation environment of 2600°C plasma, and has excellent high-temperature and long-term thermal protection capability.
[0014] The heat source for the anti-ablation test of the coating prepared by the present invention is arc plasma. Compared with oxyacetylene flame ablation, plasma ablation can usually reach higher temperature and erosion airflow pressure, which is suitable for high-temperature ablation test of materials and simulates more severe conditions. It can evaluate the ablation performance of the coating under more severe conditions. Plasma ablation experiments usually have high controllability and can accurately adjust parameters such as plasma temperature and flow rate to better simulate the ablation conditions under different working conditions. In addition, plasma ablation can provide higher energy density, so it can better simulate the impact and ablation of high-speed fluids such as high-speed inlet airflow and rocket nozzle jet on the material surface, which is more in line with actual usage scenarios.
[0015] As a preferred technical solution of the present invention, the particle size of the hafnium carbide powder is 100-500nm.
[0016] Preferably, the purity of the hafnium carbide powder is ≥99.9%.
[0017] As a preferred technical solution of the present invention, the particle size of the hafnium nitride powder is 100-500nm.
[0018] Preferably, the purity of the hafnium nitride powder is ≥99.9%.
[0019] As a preferred technical solution of the present invention, the speed is controlled to be 800-1500r / min during the mechanical mixing.
[0020] Preferably, the mechanical mixing time is 1-2 min.
[0021] Preferably, the mechanical mixing is performed at least 7 times, with an interval of 5-6 minutes between adjacent mechanical mixings.
[0022] As a preferred technical solution of the present invention, the mixed powder comprises, by mole percentage, 75-80% hafnium carbide and 20-25% hafnium nitride.
[0023] As a preferred technical solution of the present invention, the heating rate of the vacuum hot pressing sintering is 10-12°C / min.
[0024] Preferably, the holding time of the vacuum hot pressing sintering is 30-100 minutes.
[0025] In a second aspect, the present invention provides a thermal spray powder of a hafnium carbonitride material. The thermal spray powder of the hafnium carbonitride material is obtained by crushing the hafnium carbonitride material of the first aspect and then sieving it to obtain a hafnium carbonitride material spray powder with a particle size of less than 53 μm.
[0026] In a third aspect, the present invention provides a use of the thermal spray powder of the hafnium carbonitride material as described in the second aspect, wherein the use comprises preparing an atomic-level solid solution hafnium carbonitride coating using the thermal spray powder of the hafnium carbonitride material.
[0027] As a preferred technical solution of the present invention, the use includes supersonic plasma spraying of hafnium carbonitride thermal spray powder on the surface of the substrate to obtain an atomic-level solid solution hafnium carbonitride coating.
[0028] As a preferred technical solution of the present invention, the flow rate of the main gas in the supersonic plasma spraying is 50-65 L / min.
[0029] Preferably, the flow rate of the auxiliary gas in the supersonic plasma spraying is 20-25 L / min.
[0030] Preferably, the operating voltage of the supersonic plasma spraying is 90-110V.
[0031] Preferably, the operating current of the supersonic plasma spraying is 700-800A.
[0032] Preferably, the powder feeding speed of the supersonic plasma spraying is 8-15 g / min.
[0033] Preferably, in the supersonic plasma spraying, the distance between the spray gun nozzle and the substrate surface is 80-110 mm.
[0034] Compared with the prior art solutions, the present invention has the following beneficial effects:
[0035] (1) The hafnium carbonitride material of the present invention is prepared by hot pressing and sintering. By controlling the process parameters of hot pressing and sintering, such as temperature, pressure and time, the organizational structure of the hafnium carbonitride ceramic can be regulated, and the density of the prepared hafnium carbonitride block can reach more than 95%. Atomic-level solid solution hafnium carbonitride block material with a diameter of up to 50 mm can be hot pressed and sintered.
[0036] (2) The supersonic plasma spraying technology used in the present invention has a power of up to 68 kW. Compared with the currently reported plasma spraying technology (usually not exceeding 55 kW), the generated high-energy plasma heat source has a higher energy density, which can better melt the hafnium carbonitride powder material and the process parameters can be precisely controlled, thereby obtaining a high-quality, high-performance hafnium carbonitride ultra-high temperature thermal protective coating.
[0037] (3) After being ablated by plasma at a temperature of up to 2600° C. for 80 seconds, the hafnium carbonitride coating material of the present invention can effectively protect the refractory tungsten substrate from damage and failure; therefore, the hafnium carbonitride coating material has excellent thermal protection capability at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is a cross-sectional scanning electron microscopic morphology photograph of the sample obtained after vacuum hot pressing sintering in Example 1 of the present invention;
[0039] Figure 2 is a cross-sectional XRD diagram of the sample obtained after vacuum hot pressing sintering in Example 1 of the present invention;
[0040] Figure 3 is a photograph of the powder obtained after pulverization of Example 1 of the present invention;
[0041] Figure 4 is a cross-sectional microscopic morphology photograph of the coating obtained in Example 1 of the present invention;
[0042] Figure 5 is the ablation temperature curve of the coating obtained in Example 1 of the present invention;
[0043] Figure 6 This is a macroscopic photograph of the coating obtained in Example 1 of the present invention before ablation;
[0044] Figure 7 This is a macroscopic photograph of the coating obtained in Example 1 of the present invention after ablation;
[0045] Figure 8 is a cross-sectional microscopic morphology photograph of the coating obtained in Example 2 of the present invention;
[0046] Fig. 9 This is a macroscopic photograph of the coating obtained in Example 2 of the present invention after ablation.
[0047] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION
[0048] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:
[0049] This embodiment provides a method for preparing a hafnium carbonitride material, the preparation method comprising:
[0050] Mechanically mixing hafnium carbide powder and hafnium nitride powder to obtain mixed powder;
[0051] The obtained mixed powder is subjected to vacuum hot pressing and sintering to obtain a hafnium carbonitride material;
[0052] The absolute vacuum degree of the vacuum hot pressing sintering is ≤0.1 mbar;
[0053] The holding temperature of the vacuum hot pressing sintering is 2000-2200°C;
[0054] The pressure applied during the vacuum hot pressing sintering is 35-45 MPa.
[0055] In the present invention, the absolute vacuum degree of the vacuum hot pressing sintering is ≤0.1 mbar, for example, it can be 0.1 mbar, 0.09 mbar, 0.08 mbar, 0.07 mbar, 0.06 mbar, 0.05 mbar, 0.04 mbar, 0.03 mbar, 0.02 mbar or 0.01 mbar, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0056] In the present invention, the insulation temperature of the vacuum hot pressing sintering is 2000-2200°C, for example, it can be 2000°C, 2020°C, 2040°C, 2060°C, 2080°C, 2100°C, 2120°C, 2140°C, 2160°C, 2180°C or 2200°C, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0057] In the present invention, the pressure applied for vacuum hot pressing sintering is 35-45MPa, for example, it can be 35MPa, 36MPa, 37MPa, 38MPa, 39MPa, 40MPa, 41MPa, 42MPa, 43MPa, 44MPa or 45MPa, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0058] Wherein, the particle size of the hafnium carbide powder is 100-500nm.
[0059] Wherein, the purity of the hafnium carbide powder is ≥99.9%.
[0060] Wherein, the particle size of the hafnium nitride powder is 100-500nm.
[0061] Wherein, the purity of the hafnium nitride powder is ≥99.9%.
[0062] In the present invention, the particle size of hafnium carbide and hafnium nitride powders is limited to aggregates of particles of any particle size within the range that meets the specified requirements, such as aggregates of particles of uniform particle size or aggregates of particles of all particle sizes within a certain range, illustratively, such as aggregates of particles with a particle size of 100nm, such as aggregates of particles with a particle size of 200nm, such as aggregates of particles with a particle size of 300nm, such as aggregates of particles with a particle size of 400nm, such as aggregates of particles with a particle size of 500nm, and aggregates of all particles within the particle size range of 100-200nm, and aggregates of all particles within the particle size range of 150-250nm, and aggregates of all particles within the particle size range of 200-300nm, and aggregates of all particles within the particle size range of 250-350nm, and aggregates of all particles within the particle size range of 300-400nm, and aggregates of all particles within the particle size range of 150-300nm, etc.
[0063] Wherein, the controlled speed in the mechanical mixing is 800-1500r / min, for example, it can be 800r / min, 850r / min, 900r / min, 950r / min, 1000r / min, 1050r / min, 1100r / min, 1150r / min, 1200r / min, 1250r / min, 1300r / min, 1350r / min, 1400r / min, 1450r / min or 1500r / min, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0064] In the present invention, dual-center mixing and dispersion is adopted in mechanical mixing, which relies on the superposition of high-speed rotating revolution and rotation. Precision machining technology ensures that the turntable can automatically balance under high-speed unbalanced rotation, and does not need to load balancing weights, so that an extremely efficient mixing process can be achieved; it is suitable for a very wide range of applications and can quickly and evenly mix powders within a few seconds; the existing ball milling dispersion technology takes a long time (usually not less than 6 hours), has a high material loss (at least 5%), and will introduce a certain amount of impurities (mainly from the ball mill and the grinding balls).
[0065] The mechanical mixing time is 1-2 min, for example, 1 min, 1.2 min, 1.4 min, 1.6 min, 1.8 min or 2 min, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0066] In the present invention, the time for mechanical mixing is limited to the time for single mixing.
[0067] The mechanical mixing is performed at least 7 times, with an interval of 5-6 minutes between adjacent mechanical mixings, such as 5 minutes, 5.2 minutes, 5.4 minutes, 5.6 minutes, 5.8 minutes or 6 minutes, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0068] The mixed powder comprises, by mole percentage, 75-80% hafnium carbide and 20-25% hafnium nitride.
[0069] In the present invention, the molar percentage of hafnium carbide and hafnium nitride in the mixed powder is 100%.
[0070] In the present invention, the molar percentage of hafnium carbide in the mixed powder is 75-80%, for example, it can be 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, 78%, 78.5%, 79%, 79.5% or 80%, etc., but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0071] In the present invention, the molar percentage content of hafnium nitride in the mixed powder is 20-25%, for example, it can be 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5% or 25%, etc., but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0072] Among them, the heating rate of the vacuum hot pressing sintering is 10-12°C / min, for example, it can be 10°C / min, 10.2°C / min, 10.4°C / min, 10.6°C / min, 10.8°C / min, 11°C / min, 11.2°C / min, 11.4°C / min, 11.6°C / min, 11.8°C / min or 12°C / min, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0073] The holding time of the vacuum hot pressing sintering is 30-100 min, for example, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min or 100 min, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0074] In the present invention, the mixed powder is placed in a mold for sintering during vacuum hot pressing. In order to facilitate the separation of the sintered product and the mold, graphite paper or an agent that is easy to demould can be used for treatment. The choice of the mold is based on the size of the final sintered body.
[0075] Furthermore, the present invention provides a hafnium carbonitride material spray powder, wherein the hafnium carbonitride material spray powder is obtained by crushing the aforementioned hafnium carbonitride material and then sieving it to obtain the hafnium carbonitride material spray powder with a particle size of less than 53 μm.
[0076] In the present invention, the aforementioned hafnium carbonitride material can be crushed by using a commonly used crushing equipment in the art. For example, a laboratory-grade small jaw crusher is used to crush small batches of powder. The movable jaw and the fixed jaw in the jaw crusher repeatedly squeeze the block, which can achieve efficient crushing. The structure is relatively simple, and maintenance and operation are relatively easy. It is convenient to crush small batches of powder (small blocks of at least 100g) at the laboratory level, so as to quickly screen the material system. The jaw crusher can complete the crushing in 10 seconds, which is more efficient than ball milling and other methods.
[0077] In the present invention, an ultrasonic vibrating screen machine is used for screening, and the ultrasonic frequency is controlled to be 30-50kHz during the screening process.
[0078] In the present invention, after screening, drying can be performed to remove moisture from the powder. During drying, the drying temperature is controlled to be 90-100° C. and the drying time is 3-4 hours. Furthermore, in order to avoid oxidation of the powder, the powder can be dried in a vacuum environment.
[0079] Furthermore, the present invention provides a use of a hafnium carbonitride material spray powder, specifically a method for preparing an atomic-level solid solution hafnium carbonitride coating, and the specific preparation process is as follows:
[0080] The hafnium carbonitride material powder is sprayed on the surface of the substrate by supersonic plasma spraying to obtain an atomic-level solid solution hafnium carbonitride coating.
[0081] Wherein, the flow rate of the main gas in the supersonic plasma spraying is 50-65 L / min, for example, it can be 50 L / min, 51 L / min, 52 L / min, 53 L / min, 54 L / min, 55 L / min, 56 L / min, 57 L / min, 58 L / min, 59 L / min, 60 L / min, 61 L / min, 62 L / min, 63 L / min, 64 L / min or 65 L / min, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0082] Among them, the flow rate of the auxiliary gas in the supersonic plasma spraying is 20-25L / min, for example, it can be 20L / min, 20.5L / min, 21L / min, 21.5L / min, 22L / min, 22.5L / min, 23L / min, 23.5L / min, 24L / min, 24.5L / min or 25L / min, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0083] In the present invention, the main gas used in supersonic plasma spraying can be selected from argon and other main gases commonly used in the art.
[0084] In the present invention, the auxiliary gas used in supersonic plasma spraying can be selected from nitrogen and other secondary gases commonly used in the art.
[0085] Among them, the operating voltage of the supersonic plasma spraying is 90-110V, for example, it can be 90V, 92V, 94V, 96V, 98V, 100V, 102V, 104V, 106V, 108V or 110V, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0086] Among them, the working current of the supersonic plasma spraying is 700-800A, for example, it can be 700A, 710A, 720A, 730A, 740A, 750A, 760A, 770A, 780A, 790A or 800A, but is not limited to the listed values, and other unlisted values within the range also meet the requirements.
[0087] The powder feeding speed of the supersonic plasma spraying is 8-15 g / min, but is not limited to the listed values, and other values not listed within the range also meet the requirements.
[0088] Among them, the distance between the spray gun nozzle and the substrate surface in the supersonic plasma spraying is 80-110mm, for example, it can be 80mm, 85mm, 90mm, 95mm, 100mm, 105mm or 110mm, but is not limited to the listed values, and other unlisted values within this range also meet the requirements.
[0089] Furthermore, in order to illustrate the good performance of the hafnium carbonitride material obtained by the preparation method of the hafnium carbonitride material provided by the present invention, an actual example is used for illustration, as follows:
[0090] Example 1
[0091] This embodiment provides a preparation process of a hafnium carbonitride coating, which is specifically as follows:
[0092] Step 1: Weigh the original powder and mix
[0093] Weigh 200g of hafnium carbide powder and hafnium nitride powder according to a molar ratio of 76:24, add the mixed powder into a powder mixing tank, and mix the powders evenly with a dual-center high-speed powder mixer. The mixing speed is 1000r / min, and the mixing is 1min. This is performed 7 times in total, with an interval of 5min each time. Among them, the particle size of HfC powder is 100nm-500nm, and the purity is 99.9%; the particle size of HfN powder is 100nm-500nm, and the purity is 99.9%;
[0094] Step 2: Vacuum hot pressing sintering
[0095] First, the mixed raw material powder was loaded into a Φ50 graphite mold, and graphite paper with a thickness of 0.3 mm was placed at the contact point between the upper and lower die punches and the inner wall of the mold; before starting sintering, the vacuum degree in the furnace chamber dropped to 0.1 mbar, and then the sintering temperature reached 2200°C at a heating rate of 10°C / min, and a pressure of 40 MPa was applied to keep the temperature for 90 minutes; after the insulation was completed, the sample was cooled to room temperature with the furnace, and the density reached 96%; its cross-sectional scanning electron microscopy morphology image and X-ray diffraction phase map are shown as follows: Figure 1 and Figure 2 As shown;
[0096] Step 3: Block crushing
[0097] The hafnium carbonitride ceramic block obtained by hot pressing and sintering is machined to remove the graphite paper adhering to the surface, and then placed in a jaw crusher to be crushed into powder;
[0098] Step 4: Powder post-processing
[0099] The crushed powder was sieved with an ultrasonic vibrating screen machine and a 280-mesh standard screen at an ultrasonic frequency of 40kHz. The sieved powder was dried at 100°C for 3 hours to obtain high-quality single-phase face-centered cubic carbonitride powder with a particle size of less than 53μm that can be used for supersonic plasma spraying; the powder scanning electron microscopy morphology is as follows Figure 3 shown.
[0100] Step 5: Prepare the coating
[0101] The ultra-high temperature thermal protective coating of hafnium carbonitride was prepared on the substrate surface by supersonic plasma spraying. The forming quality of the coating was optimized by adjusting the process parameters during the experiment. The flow rate of the main gas argon was 60L / min, and the flow rate of the secondary gas nitrogen was 25L / min; the voltage was 93V, the current was 750A, the powder feeding speed was 10g / min, and the spraying distance was 110mm;
[0102] The prepared coating was ablated continuously for 80 seconds under 2600℃ plasma. The cross-sectional microstructure of the coating was as follows: Figure 4 As shown in Figure 2, the temperature curve of the ablation process is as follows: Figure 5 As shown in Figure 2, the macroscopic morphology of the coating surface before and after ablation is as follows: Figure 6 and Figure 7 As shown in the figure, the coating was oxidized as a whole, and point-like burn-through occurred in the center of the coating ablation, further radiating to the surrounding area. After cooling, the oxide layer in the center of the coating ablation peeled off, but the substrate was not damaged.
[0103] Example 2
[0104] This embodiment provides a preparation process of a hafnium carbonitride coating, which is specifically as follows:
[0105] Step 1: Weigh the original powder and mix
[0106] Weigh 180g of hafnium carbide powder and hafnium nitride powder according to a molar ratio of 76:24, add the mixed powder into a powder mixing tank, and mix the powders evenly with a dual-center high-speed powder mixer at a mixing speed of 1100r / min for 1min, for a total of 7 times, with an interval of 5min each time; wherein the particle size of HfC powder is 100nm-500nm, and the purity is 99.9%; the particle size of HfN powder is 100nm-500nm, and the purity is 99.9%;
[0107] Step 2: Vacuum hot pressing sintering
[0108] First, the mixed raw material powder is loaded into a Φ50 graphite mold, and a graphite paper with a thickness of 0.3mm is placed at the contact point between the upper and lower die punches and the inner wall of the mold; before starting sintering, the vacuum degree in the furnace chamber is reduced to 0.1mbar, and then the sintering temperature is reached to 2150℃ at a heating rate of 10℃ / min, and a pressure of 35MPa is applied for 30min of insulation. After the insulation is completed, the sample is cooled to room temperature with the furnace, and the density reaches 95%;
[0109] Step 3: Block crushing
[0110] The hafnium carbonitride ceramic block obtained by hot pressing and sintering is machined to remove the graphite paper adhering to the surface, and then placed in a jaw crusher to be crushed into powder;
[0111] Step 4: Powder post-processing
[0112] The crushed powder is sieved with an ultrasonic vibrating screen machine and a 280-mesh standard screen at an ultrasonic frequency of 40kHz. The sieved powder is dried at 100°C for 3 hours to obtain high-quality single-phase face-centered cubic hafnium carbonitride powder with a particle size of less than 53μm that can be used for supersonic plasma spraying;
[0113] Step 5: Prepare the coating
[0114] The ultra-high temperature thermal protective coating of hafnium carbonitride was prepared on the substrate surface by supersonic plasma spraying. The forming quality of the coating was optimized by adjusting the process parameters during the experiment. The flow rate of the main gas argon was 60L / min, and the flow rate of the secondary gas nitrogen was 20L / min; the voltage was 90V, the current was 750A, the powder feeding speed was 10g / min, and the spraying distance was 90mm; the cross-sectional micromorphology of the obtained coating is shown in Figure 8 As shown;
[0115] The prepared coating was continuously ablated under 2600℃ plasma. When the ablation lasted for 80s, the macroscopic morphology of the coating was as follows: Fig. 9 As shown, the upper edge of the coating peels off, but there is no obvious change in the ablation center, and the coating still protects the refractory metal W substrate from oxidation and ablation damage.
[0116] Example 3
[0117] This embodiment provides a preparation process of a hafnium carbonitride coating, which is specifically as follows:
[0118] Step 1: Weigh the original powder and mix
[0119] Weigh 180g of hafnium carbide powder and hafnium nitride powder according to a molar ratio of 75:25, add the mixed powder into a powder mixing tank, and mix the powders evenly with a dual-center high-speed powder mixer at a mixing speed of 1500r / min for 2min, for a total of 7 times, with an interval of 6min each time; wherein the particle size of HfC powder is 200nm-300nm, and the purity is 99.9%; the particle size of HfN powder is 400nm-500nm, and the purity is 99.9%;
[0120] Step 2: Vacuum hot pressing sintering
[0121] First, the mixed raw material powder is loaded into a Φ50 graphite mold, and a 0.3mm thick graphite paper is placed at the contact point between the upper and lower die punches and the inner wall of the mold; before starting sintering, the vacuum degree in the furnace chamber is reduced to 0.1mbar, and then the sintering temperature is reached to 2000℃ at a heating rate of 12℃ / min, and a pressure of 45MPa is applied for 100min of insulation. After the insulation is completed, the sample is cooled to room temperature with the furnace, and the density reaches 95.3%;
[0122] Step 3: Block crushing
[0123] The hafnium carbonitride ceramic block obtained by hot pressing and sintering is machined to remove the graphite paper adhering to the surface, and then placed in a jaw crusher to be crushed into powder;
[0124] Step 4: Powder post-processing
[0125] The crushed powder is sieved with an ultrasonic vibrating screen machine and a 280-mesh standard screen at an ultrasonic frequency of 40kHz. The sieved powder is dried at 100°C for 3 hours to obtain high-quality single-phase face-centered cubic hafnium carbonitride powder with a particle size of less than 53μm that can be used for supersonic plasma spraying;
[0126] Step 5: Prepare the coating
[0127] The ultra-high temperature thermal protective coating of hafnium carbonitride was prepared on the substrate surface by supersonic plasma spraying. The forming quality of the coating was optimized by adjusting the process parameters during the experiment. The flow rate of the main gas argon was 62L / min, and the flow rate of the secondary gas nitrogen was 22L / min; the voltage was 92V, the current was 700A, the powder feeding speed was 8g / min, and the spraying distance was 80mm;
[0128] After arc plasma ablation at 2600℃ for 80s, the surface of the prepared coating was completely oxidized, changing from gray to white. A small area of peeling occurred in the ablation center of the coating, but the substrate was not damaged.
[0129] Example 4
[0130] This embodiment provides a preparation process of a hafnium carbonitride coating, which is specifically as follows:
[0131] Step 1: Weigh the original powder and mix
[0132] Weigh 200g of hafnium carbide powder and hafnium nitride powder according to a molar ratio of 80:20, add the mixed powder into a powder mixing tank, and mix the powders evenly by a dual-center high-speed powder mixer. The mixing speed is 800r / min, and the mixing is 1.5min, for a total of 7 times, with an interval of 6.5min each time; wherein the particle size of HfC powder is 100nm-300nm, and the purity is 99.9%; the particle size of HfN powder is 200nm-400nm, and the purity is 99.9%;
[0133] Step 2: Vacuum hot pressing sintering
[0134] First, the mixed raw material powder is loaded into a Φ50 graphite mold, and a 0.3mm thick graphite paper is placed at the contact point between the upper and lower die punches and the inner wall of the mold; before starting sintering, the vacuum degree in the furnace chamber is reduced to 0.1mbar, and then the sintering temperature is reached to 2100℃ at a heating rate of 11℃ / min, and a pressure of 40MPa is applied for 60min of heat preservation. After the heat preservation is completed, the sample is cooled to room temperature with the furnace, and the density reaches 95.5%;
[0135] Step 3: Block crushing
[0136] The hafnium carbonitride ceramic block obtained by hot pressing and sintering is machined to remove the graphite paper adhering to the surface, and then placed in a jaw crusher to be crushed into powder;
[0137] Step 4: Powder post-processing
[0138] The crushed powder is sieved with an ultrasonic vibrating screen machine and a 280-mesh standard screen at an ultrasonic frequency of 40kHz. The sieved powder is dried at 100°C for 3 hours to obtain high-quality single-phase face-centered cubic hafnium carbonitride powder with a particle size of less than 53μm that can be used for supersonic plasma spraying;
[0139] Step 5: Prepare the coating
[0140] The ultra-high temperature thermal protective coating of hafnium carbonitride was prepared on the substrate surface by supersonic plasma spraying. The forming quality of the coating was optimized by adjusting the process parameters during the experiment. The flow rate of the main gas argon was 60L / min, and the flow rate of the secondary gas nitrogen was 25L / min; the voltage was 93V, the current was 800A, the powder feeding speed was 15g / min, and the spraying distance was 100mm;
[0141] After the prepared coating was ablated at 2600℃ arc plasma for 80s, the surface of the coating was completely oxidized, changing from the original gray to white. A small bulge appeared in the center of the coating ablation, which peeled off after cooling. However, the oxide layer was still attached to the substrate, so the substrate was not damaged.
[0142] It is stated that the present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0143] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0144] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0145] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a hafnium carbonitride material, characterized in that: The preparation method comprises: Mechanically mixing hafnium carbide powder and hafnium nitride powder to obtain mixed powder; The obtained mixed powder is subjected to vacuum hot pressing and sintering to obtain a hafnium carbonitride material; The absolute vacuum degree of the vacuum hot pressing sintering is ≤0.1 mbar; the insulation temperature of the vacuum hot pressing sintering is 2000-2200° C.; and the pressure applied by the vacuum hot pressing sintering is 35-45 MPa.
2. The preparation method according to claim 1, characterized in that: The particle size of the hafnium carbide powder is 100-500nm; Preferably, the purity of the hafnium carbide powder is ≥99.9%.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the hafnium nitride powder is 100-500nm; Preferably, the purity of the hafnium nitride powder is ≥99.9%.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The speed of the mechanical mixing is controlled to be 800-1500 r / min; Preferably, the mechanical mixing time is 1-2 min; Preferably, the mechanical mixing is performed at least 7 times, with an interval of 5-6 minutes between adjacent mechanical mixings.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mixed powder comprises, by mole percentage, 75-80% of hafnium carbide and 20-25% of hafnium nitride.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The heating rate of the vacuum hot pressing sintering is 10-12°C / min; Preferably, the holding time of the vacuum hot pressing sintering is 30-100 minutes.
7. A thermal spraying powder of hafnium carbonitride material, characterized in that: The hafnium carbonitride thermal spray powder is obtained by crushing the hafnium carbonitride material according to any one of claims 1 to 6, and then sieving to obtain the hafnium carbonitride spray powder with a particle size of less than 53 μm.
8. The use of the hafnium carbonitride material thermal spray powder as claimed in claim 7, characterized in that: The application includes preparing an atomic-level solid solution hafnium carbonitride coating by thermal spraying powder of hafnium carbonitride material.
9. The use according to claim 8, characterized in that The use includes using hafnium carbonitride material thermal spray powder to perform supersonic plasma spraying on the surface of a substrate to obtain an atomic-level solid solution hafnium carbonitride coating.
10. The use according to claim 9, characterized in that The flow rate of the main gas in the supersonic plasma spraying is 50-65L / min; Preferably, the flow rate of the auxiliary gas in the supersonic plasma spraying is 20-25 L / min; Preferably, the operating voltage of the supersonic plasma spraying is 90-110V; Preferably, the operating current of the supersonic plasma spraying is 700-800A; Preferably, the powder feeding speed of the supersonic plasma spraying is 8-15 g / min; Preferably, in the supersonic plasma spraying, the distance between the spray gun nozzle and the substrate surface is 80-110 mm.
Citation Information
Patent Citations
Preparation method for zirconium-carbide-silicon-carbide-silicon-nitride superhigh-temperature ceramic composite material
CN104557043A
Method for preparing high-heat-conductivity boron nitride reinforced polymer based composite material
CN106366402A
Method for preparing titanium subgroup carbonitride solid solution composite ceramic material by sintering
CN113929463A
Carbon / carbon composite material surface (HfZrTi) C3 medium-entropy carbide ablation-resistant coating and preparation method thereof
CN114853506A
Ultrahigh-melting-point hafnium carbonitride powder and preparation method thereof
CN115806276A